Globalisation, Growth and Income Inequality The African Experience - Kayizzi-Mugerwa, Steve (OECD Publishing, 2001)
Efforts to get Sub-Saharan Africa back into the world economy through internationally-backed reforms have largely failed due to lack of institutions, suitable local conditions or ability to negotiate effectively for foreign aid. Powerful interests or dominant communities distorted attempts at reform in some places. Success came when globalisation was made part of boosting social development and where it revived investment and growth, helping governments to start tackling poverty. It also worked best where economic chaos had decimated potential opposition. Democratic governments could probably not have got away with such drastic measures. But globalisation was not entirely to blame for increased poverty and inequality. Social and economic problems, disease, civil war, famine and external shocks played their part and in countries thus weakened, globalisation could not reverse the decline ...
Keywords: Development